2020
DOI: 10.1002/chem.202003858
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Solid‐Phase Synthesis and Biological Evaluation of Yaku'amide B and Its Seven E/Z Isomers

Abstract: Yaku′amide B (1) inhibits cancer cell growth through a unique mechanism of action. Compound 1 binds to mitochondrial FoF1‐ATP synthase, inhibits ATP production, and enhances ATP hydrolysis. The presence of one (E)‐ and two (Z)‐α,β‐dehydroisoleucines (ΔIle) in the linear 13‐mer sequence is the most unusual structural feature of 1. To uncover the biological importance of these residues, we synthesized 1 and its seven E/Z isomers 2–8 by devising a new divergent solid‐phase strategy. Both the (E)‐ and (Z)‐ΔIle res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…In this manner, bogorol A was successfully obtained by acid-mediated cleavage from the resin. Similarly, the combination of Staudinger ligation and solid-phase synthesis provides an efficient way to yield yaku'amide B (31) [41,42] and nobilamides B (32) [43,44] and the cyclic depsipeptide nobilamide D. [43] The aromatic δ-amino acids, like p-aminobenzoic acid, and its analogues are unique building blocks contained in the natural linear peptides, such as cystobactamids, [45][46][47][48] albicidin [49,50] and coralmycin A (38). [51] Due to the low reactivity of aromatic amines in the coupling with carboxylic acids, incorporation of the aromatic δ-amino acids into the peptide chain remains challenging.…”
Section: Solid-phase Total Synthesis Of Linear Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this manner, bogorol A was successfully obtained by acid-mediated cleavage from the resin. Similarly, the combination of Staudinger ligation and solid-phase synthesis provides an efficient way to yield yaku'amide B (31) [41,42] and nobilamides B (32) [43,44] and the cyclic depsipeptide nobilamide D. [43] The aromatic δ-amino acids, like p-aminobenzoic acid, and its analogues are unique building blocks contained in the natural linear peptides, such as cystobactamids, [45][46][47][48] albicidin [49,50] and coralmycin A (38). [51] Due to the low reactivity of aromatic amines in the coupling with carboxylic acids, incorporation of the aromatic δ-amino acids into the peptide chain remains challenging.…”
Section: Solid-phase Total Synthesis Of Linear Peptidesmentioning
confidence: 99%
“…In this manner, bogorol A was successfully obtained by acid‐mediated cleavage from the resin. Similarly, the combination of Staudinger ligation and solid‐phase synthesis provides an efficient way to yield yaku'amide B ( 31 ) [41,42] and nobilamides B ( 32 ) [43,44] and the cyclic depsipeptide nobilamide D [43] …”
Section: Solid‐phase Total Synthesis Of Linear Peptidesmentioning
confidence: 99%
“…For example, the requirement for large excesses of precious intermediates that are challenging to construct attenuates the benefit offered by the high overall yield. [26] Perhaps more significant is the fact that solid-phase peptide synthesis requires a linear rather than convergent synthetic strategy. Our route complements Inoues work by avoiding excess amounts of valuable subunits and by proceeding in a convergent fashion.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Although Inoue's solid‐phase synthesis of 2 possesses some advantages such as a higher yield (9.1 %) and fewer required purifications, [5c] it also has some intrinsic limitations. For example, the requirement for large excesses of precious intermediates that are challenging to construct attenuates the benefit offered by the high overall yield [26] . Perhaps more significant is the fact that solid‐phase peptide synthesis requires a linear rather than convergent synthetic strategy.…”
Section: Figurementioning
confidence: 99%
“…2 c Recently, they have devised a solid-phase synthesis of 1b (ref. 3a ) and demonstrated that the E / Z stereochemistry of the ΔIle residues modulates its anticancer activity. 3 b…”
Section: Introductionmentioning
confidence: 99%